The senior [videorecording (DVD)] - Groupé, Larry (Angel Studios, 2026)
"At 59, Mike Flynt returns to his alma mater to take the hit that ended his college football career--and to face the regrets that have haunted him for decades. Driven by unfinished business, he risks everything for one last chance to make things right. By his side is Eileen, the wife who's stood by him through years of struggle, and Micah, the son still wrestling with his father who never seemed to understand him. As the past collides with the present, Mike must prove that courage, faith, and forgiveness can outlast time itself."--